In Vitro Lung Model Assessing the Efficacy of Surgical Sealants in Treating Alveolar Air Leaks. (2nd November 2015) - Zhang, Ruoyu; Bures, Maximilian; Höffler, Hans-Klaus; Jonigk, Danny; Haverich, Axel; Krüger, Marcus
ABSTRACT: Purpose : The lack of reliable testing methods limits the evidence-based practice of surgical sealants in treating alveolar air leak (AAL). We developed an in vitro lung model to evaluate sealants' efficacy and tested the widely used human thrombin-fibrinogen sponge, TachoSil as an example. Materials and Methods : The caudal lobe of freshly excised swine lung ( n = 10) was intubated and ventilated. A focal superficial parenchymal defect (40 × 25 mm) was created in the inflated lung. AAL was assessed with increasing inspired tidal volume (TVi). After sealant application, AAL was assessed in the same way until burst failure, defined as an AAL exceeding 20 mL. To evaluate the elasticity of the sealant, the length of defect was recorded in the inflated lung. Results : Superficial parenchymal defects resulted in AAL increasing with ascending TVi. Multiple linear regression analysis revealed strong correlation between AAL and maximal inspiratory pressure, compliance and resistance. At TVi = 400, 500, and 600 mL, TachoSil achieved sealing in ten, eight, and seven tests, respectively. As TVi increased, superficial defects were still sealed in four, two, and two tests at TVi = 700, 800, and 900 mL, respectively. The burst pressure was 42 ± 5 cmH2 O. Adhesive failures were found at the burst pressure in all tests. Concerning elasticity, TachoSil allowed an expansion of the covered lung defect of 7 ± 6 mm. Conclusions : TachoSil demonstrated a strong sealing efficiency and marked elasticity in treating AAL. These results are consistent to that of the previously published animal experiment, suggesting the reliability of the presented in vitro model.